Unified cytological reports determine the clinical management - Marcin Żelezik; Anna Michalska; Agnieszka Radowicz-Chil; Piotr Lewitowicz; Anna Nasierowska-Guttmejer (Studia Medyczne, 2019)
All types of cytological procedures bear a burden of unequivocal reports and confusion with setting a proper clinical procedure. In 1989, The Bethesda System (TBS) was introduced to resolve many concerns in the matter of unclear classification of changes in cervical cytology. The guidelines of TBS were based on the clinical data provided, the quality of the smear assessment, unification of terminology, and updated knowledge about changes underlying cell abnormalities. It is believed that both TBS and thyroid TBS inspired the members of the Papanicolaou Society of Cytology to design and publish a modern approach to pancreatic lesion description. The presented proposal created a strong foundation for clinical management and revealed a serious risk of underdiagnosis. In light of the short time since the launch of this guide, more time is needed to estimate its impact, especially since only a few clinical centres have implemented it to this day.